Comparative Effects of Selenium and Gonadotropin Supplementation on In Vitro Maturation of Bligon Goat Oocytes - Arina Dinar Nurfadilla Sastranegara; Rona Agustina; Dio Fico Felsidan Diatmono; Fransisca Gani Padmawati; Pradita Iustitia Sitaresmi; Sigit Bintara; Diah Tri Widayati (Faculty of Animal Science, Universitas Gadjah Mada, 2026)
Selenium (Se) is a novel addition to in vitro maturation (IVM) media, unlike the traditional gonadotropin hormone. This highlights the advancements in reproductive biology and potential strategies to enhance oocyte maturation. This research was conducted to determine the effect of Se and gonadotropin hormone supplementation into maturation medium on the in vitro oocyte maturation of Bligon goat. Ovaries from Bligon goats were obtained from a slaughterhouse in Special Region of Yogyakarta. High-quality oocytes (grades A and B) were retrieved through aspiration, washed, and cultured in medium beneath mineral oil. Three experimental conditions were established: 50 μL of unsupplemented medium (T0), 48 μL of medium + 2 μL of gonadotropin (T1), and 48 μL of medium + 2 μL of Se (T2). The culture process was conducted for 24 h at 39°C, 95% humidity, and 5% CO2. Oocyte maturation was evaluated based on cumulus cell expansion, and the data obtained were analyzed using One-Way ANOVA, followed by Tukey’s Post Hoc test. The results indicated that the inclusion of either Se (86.26±7.20%) or gonadotropin (88.13±7.85%) in the IVM medium significantly enhanced (p<0.05) the maturation rate compared with that of the unsupplemented group (50.09±11.90%). However, there was no significant difference (p>0.05) between the two supplements. In conclusion, both Se and gonadotropin hormones proved to be effective supplements for improving the maturation rate of Bligon goat oocytes.